The Relative Contribution of Plasma Homocysteine Levels vs. Traditional Risk Factors to the First Stroke: A Nested Case-Control Study in Rural China - Zhou, Feng; Liu, Chengzhang; Ye, Lijing; Wang, Yukai; Shao, Yan; Zhang, Guohua; Duan, Zhenpeng; Chen, Jingjuan; Kuang, Jingyun; Li, Jingyi; Song, Yun; Liu, Lishun; et al. (Frontiers in Medicine, 2022)
Background Approximately 75% of Chinese hypertensive patients have elevated homocysteine (Hcy). Its implication in risk assessment and prevention of the first stroke remains an important clinical and public health question. Methods This study was based on a community cohort recruited from 2016 to 2018 in the rural China. To maximize cost efficiency, we used a nested case-control design, including 3,533 first stroke cases and 3,533 controls matched for age ±1 years, sex, and village. Individual associations of tHcy and traditional risk factors with the first stroke were examined, and their population-attributable risks (PARs) were estimated. Results There was a significant dose-response association between first stroke and total Hcy (tHcy) levels, with adjusted odds ratios of 1.11 (95% CI: 0.97, 1.26) for tHcy 10–15 μmol/L and 1.44 (1.22, 1.69) for tHcy ≥ 15 μmol/L, all compared to tHcy < 10 μmol/L. A similar trend was found for ischemic and hemorrhagic stroke. tHcy and systolic blood pressure (SBP) were independently and additively associated with the risk of first stroke (tHcy: 1.06 [1.02, 1.1]; SBP: 1.13 [1.1, 1.16]; P-interaction, 0.889). Among the ten main risk factors examined, the top two contributors to the first stroke were SBP and tHcy, with PARs of 25.73 and 11.24%, respectively. Conclusions Elevated tHcy is the second most important contributor and acts additively with SBP to increase the risk of the first stroke. This finding underscores the importance of screening and treating elevated tHcy along with traditional risk factors to further reduce the burden of the first stroke in the high-risk populations.